Characterisation of a rat model of mechanical low back pain at an advanced stage using immunohistochemical methods - Park, Thomas Sang Woon; Khan, Nemat; Kuo, Andy; Nicholson, Janet R.; Corradini, Laura; Smith, Maree T. (Clinical and experimental pharmacology and physiology, 2021)
Chronic low back pain (LBP) has high prevalence in the adult population which is associated with enormous disability. Hence, our aim was to further characterise our LBP rat model by using immunohistological and immunohistochemical methods at an advanced stage (day 49) of the model. Male Sprague-Dawley rats were anaesthetised and their lumbar L4/L5 and L5/L6 intervertebral discs (IVDs) were punctured (0.5 mm outer diameter, 2 mm-deep) 10 times per disc. Sham-rats underwent similar surgery, but no discs were punctured. For LBP- but not sham-rats, noxious pressure hyperalgesia was fully developed in the lumbar axial deep tissues on day 21 post-surgery, which was maintained until at least day 49. In the lumbar (L4-L6) dorsal root ganglia (DRGs), somatostatin (SRIF) and the somatostatin receptor type 4 (SST4 receptor) were co-localised with substance P and IB4, markers of small diameter unmyelinated peptidergic and non-peptidergic C-fibres respectively as well as with NF200, a marker of medium to large diameter neurons. On day 49, there was increased expression of SRIF but not the somatostatin receptor type 4 (SST4 receptor) in the lumbar DRGs and the spinal dorsal horns. There were increased DRG expression levels of the putative pro-nociceptive mediators: phosphorylated p38 (pp38) mitogen-activated protein kinase (MAPK) and phosphorylated p44/p42 MAPK (pp44/pp42 MAPK) as well as pp38 MAPK expression levels in the lumbar spinal cord. Taken together, the increased expression of SRIF in the lumbar DRGs and spinal cord and its co-localisation with nociceptive fibres in DRG sections suggest a potential role of SRIF in modulating chronic mechanical LBP.